Exploration of Multiple Intelligences for High School Students in Chemistry Learning in Semarang City - Fadloli, Muhammad; Sumarti, Sri Susilogati; Mursiti, Sri (Universitas Negeri Semarang)
Theory of Multiple Intelligences in education world is less so concerned. Some chemistry teachers who teach high school students in Semarang City are not aware to this theory due to lack of references. This research aims to know the level of Multiple Intelligences of high school students in Semarang City in chemistry studies according to the indicators as described by Howard Gardner. Those indicators are intelligences of verbal-linguistic, logical-mathematical, visual-spatial, physical-kinesthetic, musical-rhytmic, intrapersonal, interpersonal, and naturalist. This research is conducted in three schools which takes fifty students of XI IPA from each school using random and simple in retrieving the data. That data is collected using questionnaires which are shared to students to know the level of Mutiple Intelligences. The research data is analyzed descriptive-quantitatively, that quantitative data is only used as means of categorizing the level of studentsÃ¢â‚¬â„¢ intelligences. The result of this study is obtained various data on each indicator. The result of quantitatively data analysis shows that naturalist intelligence is obtained at the highest percentage of 71.10%, while verbal-linguistic intelligence is obtained at the lowest percentage of 62.23%. The result of this research can be used as a reference and consideration of high school teachers in formulating a lesson plan that will be applied in chemistry learning. Based on the result of this research, it can be concluded that the level of studentsÃ¢â‚¬â„¢ Multiple Intelligence in chemistry learning is averagely categorized as Ã¢â‚¬Å“hight levelÃ¢â‚¬Â.